(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article emphasizes that with the acceleration of Scientific and technological progress, the role of science in the development of mankind will increase more and more. The most important trends in the development of science are considered in detail. The positive and negative aspects of accelerating scientific and technological progress are analyzed.